Advanced Techniques in Musculoskeletal Oncology: Perfusion, Diffusion, and Spectroscopy - Teixeira, Pedro A. Gondim; Beaumont, Marine; Gabriela, Hossu; Bailiang, Chen; Verhaeghe, Jean-luc; Sirveaux, François; Blum, Alain (Seminars in Musculoskeletal Radiology, 2015)
The imaging characterization of musculoskeletal tumors can be challenging, and a significant number of lesions remain indeterminate when conventional imaging protocols are used. In recent years, clinical availability of functional imaging methods has increased. Functional imaging has the potential to improve tumor detection, characterization, and follow-up. The most frequently used functional methods are perfusion imaging, diffusion-weighted imaging (DWI), and MR proton spectroscopy (MRS). Each of these techniques has specific protocol requirements and diagnostic pitfalls that need to be acknowledged to avoid misdiagnoses. Additionally, the application of functional methods in the MSK system has various technical issues that need to be addressed to ensure data quality and comparability. In this article, the application of contrast-enhanced perfusion imaging, DWI, and MRS for the evaluation of bone and soft tissue tumors is discussed, with emphasis on acquisition protocols, technical difficulties, and current clinical indications.
Keywords: musculoskeletal oncology; MRI; diffusion-weighted imaging; perfusion; proton spectroscopy